ANTIPATHOGENIC EFFICACY OF METHANOLIC LEAF EXTRACT OF CINNAMOMUM TAMALA (BUCH.-HAM.) AND AEGLE MARMELOS (L.) WITH THEIR NUTRITIONAL POTENTIALITY - SUKUMAR DANDAPAT , MANOJ KUMAR, AMIT KUMAR, M. P. SINHA, (The Bioscan, 2013)
Antipathogenic efficacy of methanolic leaf extract of Cinnamomum tamala (Buch.-Ham.) and Aegle marmelos (L.) through inhibiting the growth of Staphylococcus aureus (MTCC 3160), Salmonella typhi (MTCC 3216) and Proteus mirabilis (MTCC 7837) the causative pathogens of food poisoning, boils, abscesses, wound infection, pneumonia, toxic shock syndrome, typhoid fever, urethitis, cystitis, pylonephritis and prostatitis has been investigated. All the strains were affected by methanolic leaf extract of C. tamala and A. marmelos in agar diffusion method and broth dilution method. The MIC values in agar diffusion method were 2.5 mg/mL against S. aureus for extract of both plants and 5 mg/mL, 1.25 mg/mL, against P. mirabilis for the extract of C. tamala and A. marmelos respectively. The MIC values in broth dilution method were 2.5 mg/mL against S.aureus for both plants extract, 4 mg/mL, 1 mg/mL against P.mirabilis and 9 mg/mL, 10 mg/mL against S. typhi for C. tamala and A. marmelos respectively. The nutritional value, phytochemical contents and inorganic substance content of C. tamala is higher than A. marmelos.